Isolation and Potential of Plastic-Degrading Bacteria from Plastic Waste - Fatti, Clara; Rumampuk, Natalie Detty C.; Gerung, Grevo Soleman; Wullur, Stenly; Mamuaja, Jane Marianne; Ginting, Elvy Like (Sam Ratulangi University, 2025)
Plastic waste is an environmental issue, including in marine environments. One method of managing plastic waste is through biodegradation using bacteria. This study aims to isolate bacteria from plastic waste in Malalayang, and North Sulawesi waters, and test their potential to degrade plastic using laboratory experimental methods. Bacteria were isolated using a Nutrient Agar (NA) medium and then tested for their ability to degrade plastic using a Nutrient Broth (NB) medium containing plastic fragments. The NB medium with plastic fragments was incubated using an orbital shaker at room temperature with agitation at 130 rpm for 30 days. Five bacterial isolates were successfully obtained from plastic waste: isolates C1, C2, C3, C4, and C5. Four of the bacterial isolates were found to be capable of degrading plastic, as indicated by the reduction in the dry weight of the plastic after 30 days of incubation. The highest plastic weight reduction was shown in isolate C2, with a decrease of 2.95%, while the lowest reduction was observed in isolate C4, with a decrease of 2%. Keywords: Bacteria, Isolation, Biodegradation, Plastic. Abstrak Sampah plastik merupakan masalah lingkungan termasuk lingkungan laut. Salah satu pengelolaan sampah plastik adalah melalui biodegradasi menggunakan bakteri. Penelitian ini bertujuan mengisolasi bakteri dari sampah plastik Perairan Malalayang, Sulawesi Utara dan melakukan uji potensi bakteri tersebut dalam mendegradasi plastik menggunakan metode eksperimen laboratorium. Bakteri diisolasi menggunakan medium Nutrient Agar (NA), kemudian diuji kemampuan mendegradasi plastik dengan menggunakan medium Nutrient Broth (NB) yang berisi potongan plastik. Medium NB berisi potongan plastik diinkubasi menggunakan orbital shaker pada suhu ruang dengan agitasi 130 rpm selama 30 hari. Lima isolat bakteri berhasil diisolasi dari sampah plastik, yaitu isolat C1, C2, C3, C4 dan C5. Didapatkan empat isolat bakteri yang mampu mendegradasi plastik, yang ditunjukkan dengan pengurangan berat kering plastik setelah diinkubasi selama 30 hari. Pengurangan berat plastik tertinggi ditunjukkan oleh isolat C2 sebesar 2,95 %, sedangkan pengurangan berat terendah oleh isolat C4 sebesar 2 %. Kata kunci: Bakteri, Isolasi, Biodegradasi, Plastik.